Pengaruh Flipped Classroom Dan Literasi Digital Terhadap Penguasaan Konsep Sosiologi Materi Integrasi Sosial - Nugrahani, Ruth Heradityas; Kuswandi, Dedi; Wedi, Agus (Universitas Negeri Malang, 2023)
Learning sociology, need an effective strategy to succeed in building a deep concept of the main study that including the social life of the community. The teacher's teaching method is in the same direction, resulting in boredom. The lack of appropriateness of illustrations in reading sources with the current situation of society, requires teachers to use other references such as articles, news, videos on the internet. Digital literacy have important role in discovering and filtering information, managing digital media. For deepening the concepts and studies, it takes more study time and a learning environment that facilitates these needs. Students from a high school in Surakarta who are in class XI are the focus of the quasi-experimental research. Concept mastery tests and digital literacy questionnaires are the instruments used. The results of the analysis test stated that there was differences in mastery of concepts between groups of students who apply the flipped classroom strategy and discovery learning affected by digital literacy. Application of flipped classroom took more benefit for students with the availability of a lot of time and facilitated independent learning such as interacting with learning videos, understanding, and exploring other resources before studying in class. Activities in class are more focused on discussions enriching the understanding that was previously owned, so that mastery of concepts is developed through learning experiences and exchange of information to improve thinking skills in solving problems from case studies.AbstrakDalam pembelajaran Sosiologi diperlukan strategi efektif agar berhasil membangun konsep yang kuat terhadap kajian pokok yang mencakup kehidupan sosial masyarakat. Metode ajar guru yang searah, mengakibatkan kejenuhan. Kurang sesuainya ilustrasi pada sumber bacaan dengan situasi masyarakat terkini, menuntut guru perlu memanfaatkan referensi lain misalnya artikel, berita, video di internet. Literasi digital memiliki peran penting guna menyaring dan menemukan informasi, mengelola media digital. Untuk pendalaman konsep dan kajian, diperlukan waktu belajar lebih dan lingkungan belajar yang memfasilitasi kebutuhan tersebut. Peserta didik salah satu SMA Kota Surakarta yang duduk di kelas XI menjadi fokus penelitian eksperimen semu. Tes penguasaan konsep dan angket literasi digital merupakan instrumen yang digunakan. Hipotesis diuji dengan analisis kovarian berbantuan SPSS 22. Hasil uji analisis menyatakan adanya perbedaan penguasaan konsep antara kelompok peserta didik yang menerapkan strategi flipped classroom dan discovery learning yang dipengaruhi oleh literasi digital. Penerapan flipped classroom menguntungkan peserta didik dengan tersedianya banyak waktu dan terfasilitasinya belajar mandiri seperti berinteraksi dengan video pembelajaran, memahami, dan mengeksplorasi sumber lain sebelum belajar di kelas. Aktivitas di kelas lebih fokus pada diskusi memperkaya pemahaman yang sebelumnya dimiliki, sehingga penguasaan konsep dikembangkan melalui pengalaman belajar dan pertukaran informasi untuk meningkatkan kecakapan berpikir dalam menyelesaikan permasalahan dari studi kasus.